Taphonomic analysis of fossil concentrations from La Manga Formation (Oxfordian), Neuquén Basin, Mendoza Province, Argentina - Bressan, G.S.; Palma, R.M. (Journal of Iberian Geology, 2010)
Griphaeid-dominated fossil concentrations of La Manga Formation are characterized on the basis of taphonomic, sedimentologic, stratigraphic and palaeoecologic criteria. These concentrations are present in the basal deposits (Unit 1) of three outcrops in the locality of Bardas Blancas. Their attributes allow distinguishing seven different fossil accumulations: A) Channelized fossil concentrations of Gryphaea sp.; B) Shell beds of Gryphaea sp. highly reworked; C) Shell beds of Gryphaea sp. moderately reworked; D) Accumulations of Gryphaea sp. with biomicrite to biopelmicrite matrix; E) Shell detritus; F) Accumulations produced by bottom currents; and G) Accumulations found in clumps. Accumulations A-C were deposited by high energy processes (storm waves and currents) in the upper middle ramp. Accumulations D and E were produced by high energy processes (storm waves and currents) but the final depositions were produced out of suspension in low energy environments, in lower middle ramp settings. Accumulations F were generated by weak bottom currents, meanwhile accumulations G correspond to gryphaeids associations reworked by bioturbators or by hydraulic processes after variable periods of permanence in sediment/water interface. Both are interpreted as lower middle or outer ramp. This interpretation suggests that these deposits that in previous works were interpreted as outer ramp settings, characterize middle and outer ramp settings. The vertical distribution of fossil concentrations from upper middle ramp to lower middle and outer ramp settings evidences a continuously growing accommodation space and allows to interpret the Unit 1 as part of a transgressive systems tract.